2020
DOI: 10.1021/acs.orglett.0c02526
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity Control in Gold-Catalyzed Hydroarylation of Alkynes with Indoles: Application to Unsymmetrical Bis(indolyl)methanes

Abstract: Gold-catalyzed hydroarylation of unactivated alkynes with indoles have previously been reported to proceed with double indole addition to produce symmetrical bis­(indolyl)­methanes (BIMs). We demonstrate for the first time that the selectivity of the gold-catalyzed reaction can be fully switched to allow for isolation of the vinylindole products instead. Furthermore, this selective reaction can be utilized to synthesize the more difficult to access unsymmetrical BIMs from readily available starting materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 81 publications
(13 reference statements)
0
15
0
Order By: Relevance
“…Lee's group discussed a synthetic pathway of gold-catalyzed hydroarylation of alkynes 174 with indoles 171 (Scheme 76). 97 The reaction took place between alkynes and different substituted indoles derivatives 171 to prepare the desired products 243 in up to 96% yields under the optimized reaction conditions of 2 mol% PPh 3 AuNTf 2 catalyst and acetonitrile at 30 °C for 24 h. Both electron-withdrawing and electron-donating groups at different positions of the aryl ring of indole furnished excellent yields of the corresponding product. Generally, N -alkylation of indole gave a high yield (96%); however, in the presence of the electron-withdrawing Boc group the yield of the reaction decreased (<5%) due to the nucleophilic nature of indole.…”
Section: Intermolecular Hydroarylation Reactionmentioning
confidence: 99%
“…Lee's group discussed a synthetic pathway of gold-catalyzed hydroarylation of alkynes 174 with indoles 171 (Scheme 76). 97 The reaction took place between alkynes and different substituted indoles derivatives 171 to prepare the desired products 243 in up to 96% yields under the optimized reaction conditions of 2 mol% PPh 3 AuNTf 2 catalyst and acetonitrile at 30 °C for 24 h. Both electron-withdrawing and electron-donating groups at different positions of the aryl ring of indole furnished excellent yields of the corresponding product. Generally, N -alkylation of indole gave a high yield (96%); however, in the presence of the electron-withdrawing Boc group the yield of the reaction decreased (<5%) due to the nucleophilic nature of indole.…”
Section: Intermolecular Hydroarylation Reactionmentioning
confidence: 99%
“…To drive selectivity toward the diarylated product, addition of a Brønsted acid in a second step (Scheme 21, reaction (a)) results in the complete conversion to the diarylated product in minutes, which can be put to advantage in the production of double hydroarylation products bearing two different heteroaryl substituents. Very recently, it has been established by the group of Lee that in the case of 2,3 or 4-substituted indoles the gold-catalyzed hydroarylation reaction of arylacetylenes conveniently stops at the monohydroarylation stage using a defect of indole [122]. Steric effects are invoked to explain the lack of further reactivity.…”
Section: Selectivity: Monoarylation Versus Diarylationmentioning
confidence: 99%
“…Recently, Lee and co-workers have shown that vinyl indoles can be prepared in excellent yield from the reaction of 2-substituted indoles with an excess of alkyne at low gold catalyst loadings, although with indole itself, bis indolemethanes were still generated. 32 While this could be circumvented through the use of a 2-boryl-substituted indole and subsequent deprotection, the selective monoalkenylation of unsubstituted indole remains an unsolved challenge.…”
Section: Introductionmentioning
confidence: 99%